Japan in a Dynamic Asia : Coping with the New Security Challenges. - Satō, Y. (Yōichirō) (Studies of modern Japan., 2006)
This collection takes a unique country-by-country approach to examine Japan's relations with individual Asian countries and sub-regions. As Japan's activism increases under the Koizumi administration, Japan in a Dynamic Asia provides a timely, updated understanding of Japan's rapidly changing foreign policies in the contexts of the new regional power balance and security concerns.